STRATEGI PENGELOLAAN PRODUK PENGETAHUAN DIGITAL ‘LOCAL CONTENT’ UNTUK PENGEMBANGAN KONTEN REPOSITORI KEMENTERIAN PENDIDIKAN DAN KEBUDAYAAN REPUBLIK INDONESIA - Nashihuddin, Wahid; Amir, Chaidir (Universitas Pendidikan Indonesia, 2019)
Kajian ini sangat penting untuk peningkatan pengelolaan produk pengetahuan digital local content melalui repositori lembaga Kemendikbud. Kajian ini bertujuan untuk menjelaskan dan mengetahui: (a) pengelolaan repositori lembaga; (b) upaya pengembangan konten dan sistem repositori lembaga; (c) produk pengetahuan local content lembaga; dan (d) strategi pengelolaan produk pengetahuan local content melalui repositori lembaga Kemendikbud. Jenis data kajian adalah kualitatif, dengan sumber data studi dokumen dan observasi. Data kajian dianalisis secara deskriptif. Hasil kajian ini menunjukkan bahwa: (1) pengelolaan repositori lembaga Kemendikbud mengacu pada tugas dan fungsi Perpustakaan Khusus Instansi Pemerintah yang bertujuan untuk mengintegrasikan layanan dan koleksi perpustakaan digital local content; (2) koleksi digital local content repositori lembaga jumlahnya relatif banyak dan sudah dapat dimanfaatkan secara optimal meskipun sistem repositori masih terus dikembangkan; (3) produk pengetahuan local content repositori lembaga Kemendikbud berupa dokumen kebijakan Kemendikbud (pedoman, panduan, juklak, juknis), hasil kajian, materi diklat, hasil belajar peserta diklat, hasil penelitian, dan jurnal; (4) Perpustakaan Kemendikbud perlu menetapkan strategi dalam pengembangan sistem dan konten repositori, mulai dari strategi kebijakan pengembangan sistem hingga ke pengembangan produk pengetahuan digital local content repositori lembaga. Â Abstract. This study is very important for management improving of digital knowledge product of local content in Ministry of Education and Culture's repository. This study aims to describe and to know: (a) the management of institution repository; (b) the development efforts of the institutional repository contents and systems; (c) the knowledge product of institution local content; and (d) the management strategies of the knowledge product of local content through institution repository. The type of study data is qualitative, with the data sources are document studies and observations. The data were analyzed descriptively. The study results indicated that: (1) the management of the Ministry of Education and Culture's repository refered to the duties and functions of the Special Library of Government Agency that aims to integrate of the services and collections digital local content of library; (2) the digital collection of local content repository institutions is relatively large and can be utilized optimally even though the repository system is still being developed; (3) the knowledge products of local content of in Ministry of Education and Culture's repository such as of policy documents (guidelines, manuals, operational guidelines, technical guidelines), study results, training materials, training participants' learning outcomes, research results, and journals; (4) the library of Ministry of Education and Culture needs to establish the repository system and content development strategies, start from the policy strategies of system development to the knowledge products of digital local content in instituion repository.